MITIGASI RISIKO DALAM MEREDAM KONFLIK DI SEKOLAH [STUDI KASUS PADA TK & SD RABBANI BANDUNG] - Fauziah, Marwah; Hidayat, Wahyu (Program Studi Manajemen Pendidikan Islam, 2023)
This research aims to identify and analyze risk mitigation efforts that are effective in reducing conflict in the school environment, with a focus on case studies at Rabbani Kindergarten & Elementary School in Bandung. Conflict in schools can be detrimental to both students and teaching staff, so there is a need for measurable and targeted strategies to reduce risks and overcome these conflicts. The research method used involved observation, interviews, and document analysis to understand the context of conflict at Rabbani Kindergarten & Elementary School in Bandung. The research results show that effective risk mitigation involves a combination of conflict prevention, quick conflict handling, and the creation of an inclusive school environment. In addition, risk mitigation involves various related parties such as students, parents, and school staff in the handling process which is also a key factor in reducing potential conflicts. The school manages to create a harmonious environment by effectively managing conflicts and implementing positive initiatives. Stakeholder involvement and regular evaluations can maintain the sustainability of risk mitigation policies that have been implemented.